Forgotten Intrauterine Contraceptive Device Presenting as Vesicouterine Fistula – Migration or Misadventure - Vidhyalakshmi Ramadoss Kabilan; J. Karthiga Prabhu; Senthilkumar Thiagarajan; Divyabharathi Muthulingam; N Yashwanthini Priyankaa (Journal of Mid-Life Health, 2025)
Intrauterine contraceptive device (IUD) is one of the most commonly used long-term contraceptive methods worldwide. Migration of IUD is one of the rare complications of IUD insertion. Migrated IUD with calculus formation is a rarer long-term complication of IUD. A 55-year-old postmenopausal woman attended the outpatient clinic with complaints of continuous dribbling of urine. On examination, there was pooling of urine in the posterior fornix of the vagina, and the calcified vertical stem of the IUD was visualized through the cervical os. On evaluation, a giant calculus was noted within the bladder arising from the perforated IUD arm with vesicouterine fistula. Vesical lithotripsy followed by fistulous tract excision with repair of bladder wall was done.